Initiating DNA replication: a matter of prime importance. (15th January 2019) - Bell, Stephen D.
Abstract : It has been known for decades that the principal replicative DNA polymerases that effect genome replication are incapable of starting DNA synthesis de novo . Rather, they require a 3′-OH group from which to extend a DNA chain. Cellular DNA replication systems exploit a dedicated, limited processivity RNA polymerase, termed primase, that synthesizes a short oligoribonucleotide primer which is then extended by a DNA polymerase. Thus, primases can initiate synthesis, proceed with primer elongation for a short distance then transfer the primer to a DNA polymerase. Despite these well-established properties, the mechanistic basis of these dynamic behaviours has only recently been established. In the following, the author will describe recent insights from studies of the related eukaryotic and archaeal DNA primases. Significantly, the general conclusions from these studies likely extend to a broad class of extrachromosomal element-associated primases as well as the human primase-related DNA repair enzyme, PrimPol.